2019
DOI: 10.1128/iai.00550-19
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22 (IL-22) Binding Protein Constrains IL-22 Activity, Host Defense, and Oxidative Phosphorylation Genes during Pneumococcal Pneumonia

Abstract: Streptococcus pneumoniae is the most common cause of community-acquired pneumonia worldwide, and interleukin-22 (IL-22) helps contain pneumococcal burden in lungs and extrapulmonary tissues. Administration of IL-22 increases hepatic complement 3 and complement deposition on bacteria and improves phagocytosis by neutrophils. The effects of IL-22 can be tempered by a secreted natural antagonist, known as IL-22 binding protein (IL-22BP), encoded by Il22ra2. To date, the degree to which IL-22BP controls IL-22 in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In support of this notion, our EP transcriptome data showed that MF induced expression of signaling pathways of proinflammatory cytokines such as IL-15 and IL-22. These proinflammatory cytokines are produced mainly by inflammatory cells, including innate lymphocytes, T cells, and natural killer cells ( 26 , 27 ), and greatly contribute to the initiation and progression of inflammation status ( 27 29 ). Canonical pathway analysis showed that MF reduced the activity of the complement system in EP.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, our EP transcriptome data showed that MF induced expression of signaling pathways of proinflammatory cytokines such as IL-15 and IL-22. These proinflammatory cytokines are produced mainly by inflammatory cells, including innate lymphocytes, T cells, and natural killer cells ( 26 , 27 ), and greatly contribute to the initiation and progression of inflammation status ( 27 29 ). Canonical pathway analysis showed that MF reduced the activity of the complement system in EP.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with a barrier protective role for IL-22 in the lung. The role of IL-22 has also been studied in the context of Streptococcus pneumoniae infection (12,13). IL-22-/-mice were shown to have increased bacterial burden in the lung compared to WT mice.…”
Section: Bacterial Infectionmentioning
confidence: 99%
“…Among the differently expressed genes in the comparison of non-ICI treated rats, IL22RA2 (interleukin 22 receptor subunit alpha 2), IL2RA (interleukin 2 receptor antagonist) and IFRD1 (interferon related developmental regulator 1) were upregulated and are described as regulators of the in ammatory response [55,56]. IL-6, a pro-in ammatory cytokine produced by myeloid cells and cardiomyocytes in an autocrine mechanism [53], was also upregulated in this group.…”
Section: Discussionmentioning
confidence: 80%